Educational Interaction of Prophet Musa and Khidir in The Perspective of Al-Quran - Afrizal Syahputra (Didaktika Religia, 2020)
This research examines the meeting of the Prophet Musa and Khidir which is mentioned in the Al Qur'an in al-Kahfi. They met at a place called "Majma'al Bahrain". This meeting was motivated by Allah's admonition to Prophet Musa for considering himself the smartest and His orders that he should meet Prophet Khidir. Prophet Khidir as a teacher taught some material to Prophet Musa. His meeting with Prophet Khidir made Prophet Musa understand about inner knowledge and gain various knowledge and experiences that he had not previously obtained. The approach used in this study is a qualitative approach, and procedurally this study uses the comparison method with literature study techniques in data collection. The author uses several classical and modern Qurâ€™an interpretation books as references in this study. Research result shows that this teaching and learning process raises educational interactions which include: educational goals, educators, students, educational methods, and educational media. The educational interaction components in this study are very useful for educators and students in carrying out teaching and learning activities